Pengaruh Beban Kerja Dan Pengembangan Karir Terhadap Motivasi Dan Kepuasan Kerja (Fakultas Ekonomi Universitas Gresik, 2023)
The Ministry of Manpower has simplified the echelon 3 and 4 structural bureaucracy to functional positions of 490 employees. Based on SE BKN Number 3/SE/II/2021 the simplification of the bureaucracy consists of the position of Administrator (Echelon 3) to become the Functional Middle Expert position and the Supervisory position (Echelon 4) to become the Functional Junior Expert position. Equalization changes the organizational structure which is followed up with the Assignment of functional officials as Coordinators and Sub-coordinators as substitutes for structural positions in organizational units. The Coordinator and Sub-coordinator are given the task and function of coordination and management of activities in accordance with the field of work within the work unit which is directly responsible to the head of the organizational unit. Research using data analysis methods using PLS with a population of 127 employees with the criteria of serving as Coordinator, Subcoordinator, and Functional Employee who has 10 years working experience. From these data it was found that this simplification had an effect on Workload and Career Development on Work Motivation of functional employees who received additional assignments as Coordinators and Sub-coordinators through Job Satisfaction as a fully mediated.